The combination of baicalin and baicalein enhances apoptosis via the ERK/p38 MAPK pathway in human breast cancer cells - Zhou Qian-mei; Wang Song; Zhang Hui; Lu Yi-yu; Wang Xiu-feng; Motoo Yoshiharu; Su Shi-bing (Acta Pharmacologica Sinica, 2016)
Aim: To examine whether the cell growth inhibitory effect of the combination of baicalin and baicalein is related to apoptosis. Moreover, to determine whether the expression of some apoptosis-related proteins is regulated by the ERK/p38 MAPK pathway. Methods: Cell viability was measured using a 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was detected by acridine orange (AO) staining, DNA ladder assay and flow cytometric analysis. Apoptosis-related proteins were observed using Western blot analysis. Results: Compared with baicalin or baicalein alone, the combination treatment of baicalin (50 μmol/L) and baicalein (25 μmol/L) had an anti-proliferative effect in a time-dependent manner. Isobologram analysis demonstrated that the combination treatment had a synergistic effect. Moreover, apoptosis in MCF-7 cells was increased by 12% and 20% with the combination treatment at 24 h and 48 h, respectively. With the combination treatment in MCF-7 cells, cleaved caspase-3 and caspase-9 were observed, and the level of bcl-2 expression was decreased approximately 20% and 40% at 24 h and 48 h, respectively. The expression of bax and p53 were increased about 25% and 15% at 48 h, respectively. Moreover, the activation of caspase-3, -9 and the regulation of bcl-2, bax and p53 were related to ERK /p38 MAPK activation. Conclusion: In this study, apoptosis was enhanced by the combination treatment of baicalin and baicalein, which activated caspases-3 and caspase-9, downregulated the level of bcl-2 and upregulated the level of bax or p53 via the ERK/p38 MAPK pathway.